2022
DOI: 10.1186/s12967-022-03643-w
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant medication of cetirizine in advanced melanoma could enhance anti-PD-1 efficacy by promoting M1 macrophages polarization

Abstract: Background The clinical observation showed a potential additive effect of anti-PD-1 agents and cetirizine in patients with advanced melanoma. Methods Clinical outcomes of concomitant cetirizine/anti-PD-1 treatment of patients with stage IIIb–IV melanoma were retrospectively collected, and a transcriptomic analysis was performed on blood samples obtained at baseline and after 3 months of treatment. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In fact, even a molecule such as cetirizine can be combined with anti-PD1 to improve its efficacy. In a retrospective study [74] on patients with stage IIIb-IV melanoma, the cetirizine/anti-PD1 combination, including pembrolizumab, showed a better PFS and OS than treatment without cetirizine. This may be explained by the polarization of M1 macrophages induced by cetirizine, enhancing the anti-PD1 immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, even a molecule such as cetirizine can be combined with anti-PD1 to improve its efficacy. In a retrospective study [74] on patients with stage IIIb-IV melanoma, the cetirizine/anti-PD1 combination, including pembrolizumab, showed a better PFS and OS than treatment without cetirizine. This may be explained by the polarization of M1 macrophages induced by cetirizine, enhancing the anti-PD1 immune response.…”
Section: Discussionmentioning
confidence: 99%
“…As a limitation of our approach, clinical validation for the therapeutic utility of our concept has only been obtained for ICD inducers in prospective clinical trials, 72–76,80 while most of the evidence is based on retrospective analyses 13,26,61–70 . Clinical evidence in favor of the use of T‐cell stimulators is based on retrospective observations and is merely correlative 86,90–94 . Finally, there is no strong clinical evidence yet in favor of the potential utility of ICD enhancers for cancer treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Second, retrospective epidemiological analyses indicate that use of specific antihistamines (including astemizole) is associated to overall survival of patients with localized ovarian cancer 91 and any type of metastatic cancers 92 . Third, the use of antihistamines has been linked to favorable outcome of immunotherapy in analyses focusing on melanoma 93 and non‐small cell lung cancer patients, 90 as well as in a pan‐cancer analysis 94 . Fourth, in a basket trial involving patients with breast, colon, or lung cancer, clinical responses to PD‐1 blockade negatively correlated with histamine levels in the blood 90 .…”
Section: Screening For T‐cell Stimulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved cancer survival was associated with the administration of the antihistamine desloratadine, specifically in patients with tumors that respond to therapy with immune checkpoint inhibitors, while lower evidence was found for CTZ, which was only observed in gastric, pancreatic, and ovarian cancer [ 86 ]. However, others showed that the concomitant use of CTZ and anti-PD-1 monoclonal antibodies led to increased progression-free survival in patients with stage IIIb-IV melanoma, suggesting that the effect of CTZ may synergize with immunotherapies enhancing its efficacy [ 87 ].…”
Section: Vanadium Complexed With Marketed-approved Drugsmentioning
confidence: 99%